Jobs Incorporated: Incorporation Status and Job Creation - Thomas Åstebro; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2015)
Recent research has shown that entrepreneurs who start incorporated firms are fundamentally different from entrepreneurs who start sole proprietorships. This difference suggests that incorporation status may distinguish the self-employed with no ambition to hire from entrepreneurs who plan to hire others.In this paper, we show that this intuition is correct. Using a dataset with over 24 million observations and more than 230,000 entries into entrepreneurship, we show that newly incorporated entrepreneurs create 50% more jobs than sole proprietors. The result derives from the fact that high-ability individuals are more likely to form incorporated ventures. While there is selection from both tails of the ability distribution into starting incorporated ventures - that is, both stars and misfits start corporations - it is primarily individuals with low ability, the misfits, who start sole proprietorships. This does not, however, mean that the aggregate number of jobs created by the incorporated is higher. Since more entrepreneurs in total become sole propri etors, the sole proprietors initially contribute more to aggregate job creation than the incorporated.
Keywords: J24; L26; 330; Entrepreneurship; Incorporation; Job creation; Occupational choice; Self-employment; Stars and misfits